Elements of Culture of Reference in Translation / Elemente der Bezugskultur in der Übersetzung - Wille, Lucyna (Kalbotyra, 2009)
The paper presents the translator’s decisions regarding elements of foreign culture as examples from the novels Memory of my Melancholy Whores by G.G. Marquez and Fury by S. Rushdie, both in three translations. In the theoretical part the established termAusgangskultur (source culture) is replaced by Bezugskultur (culture of reference) in order to avoid suggestion of granted identity between culture and language. It is shown that all translators in general aim at the reader’s conformity but are not consequent at all regarding the strategy of rendering the elements of foreign culture. The technique overrules the strategy; each of the analyzed translations contains transportations of foreign elements, explanations of the latter and cases of their replacing by domestic phenomena.